Estudo de catalisadores de ferro promovidos com potássio ou manganês e suportados em peneiras moleculares do tipo SBA-15 e SBA-16 aplicados na síntese de Fischer-Tropsch - Silva, Diogo Pimentel de Sá da (2023)
This research was divided into two stages. In the first stage, the performance of different structural promoters from the SBA family (SBA-15 and SBA-16) with 20 wt.% of iron (Fe) was evaluated in the Fischer-Tropsch Synthesis (FTS). In the second stage, on the best structural support, high amounts of active phase (10%, 20%, and 30% wt.) were deposited, and the performance of potassium (K) and manganese (Mn) as promoters for Fe was also examined in the CO hydrogenation reaction. In the first stage, the physicochemical characterizations performed revealed that the high surface area and pore volume of SBA-15 led to the formation of smaller hematite crystallites (α-Fe2O3 around 6.1 nm), thereby increasing the metal-support interaction and favoring the crystallization of the gamma phase fayalite (γ-Fe2SiO4, a silicate of iron with high thermal and mechanical stability). Thus, the catalyst 20Fe/SBA-16, with a larger α-Fe2O3 crystallite size (11.0 nm) and appropriate metal-support interaction, exhibited higher CO conversion (24.8%), C5+ selectivity (61.0%), and lower production of CH4 (11.3%) and CO2 (7.9%) compared to 20Fe/SBA-15. In the second stage, the evaluation of the catalyst with different iron proportions (Fe/SBA-16), not reported in the literature for FTS, revealed that the 20 wt.% content of the active phase was suitable for reducing the metal-support interaction and suppressing pore blocking at high Fe loads. The promotion of 1 wt.% of Mn in the 20Fe/SBA-16 catalyst decreased CO2 production (from 7.9% to 4.3%), CH4 (from 11.3% to 7.6%), and increased selectivity for aviation bio-kerosene (hydrocarbons between C8−C18), rising from 45.3% to 55.4%. This improvement may be related to the higher content of Hägg carbide, identified as the most active catalytic site for FTS. Meanwhile, the promotion of 1 wt.% of K in the Fe catalyst increased selectivity for CO2 (from 7.9% to 14.7%) due to higher activity in the water-gas shift reaction. Therefore, this study concluded that the catalyst promoted with 1 wt.% Mn and 20 wt.% Fe supported on SBA-16 was the most active material for aviation bio-kerosene production, associated with low selectivity for CO2.